Publishing Fake Information Online-Case of Online Vietnam Magazines (Thanhnien Newspaper, Tuoi tre newspaper, Vietnamnet.vn, dantri.com.vn, giaoduc.edu.vn, sctv.com.vn, etc.) From an Approach of German and EU Laws and Cybersecurity Regulations - Le Huong Hoa, PhD; Dinh Tran Ngoc Huy; Bui Thi Thu, PhD; Dinh Tran Ngoc Hien (International Journal of Business and Social Science Research, 2022)
Publishing fake information have at least three bad effects on the community: creating disinformation, anxiety, and disorder in society. Still using qualitative analytical methods with synthesis and inductive methods, the authors will address 2 cases of Vietnam magazines: thanhnien. vn and tuoitre.vn, vietnamnet. vn, giaoduc.edu.vn, dantri.com.vn, (online newspapers) and recently sctv.com.vn with their issue of publishing fake news online, which increasing as a problem in recent years 2015-2020. In this paper, we also use the European approach and laws on exploring the issue of publishing and delivering false information via the internet and social media. Last but not least, the views and ideologies of V.I Lenin and Ho Chi Minh on journalism and journalists are mentioned for educating the young generation.